Variety trait preferences for traditional African vegetables in West Africa - Mitchodigni, Irene M.; Ayenan, Mathieu A.T.; Govoeyi, Benoit; N’Danikou, Sognigbe; Komlan, Christelle; Bouraima, Raoudath; Codjo, Simon; Schreinemachers, Pepijn (Frontiers in Sustainable Food Systems, 2025)
Traditional African vegetables (TAV) are increasingly acknowledged for their potential to diversify smallholder farmers’ income and improve the quality of people’s diets. Plant breeding of TAV has been very limited, but this is slowly changing. Breeding programs need information on the crop trait preferences of value chain actors. Here, we identified and prioritized trait preferences for amaranth, jute mallow, and okra in Benin and Mali using focus group discussions with farmers and individual interviews with traders and consumers. The findings show that late flowering, a high number of branches, suitability for multiple harvesting, broad leaves, and green to dark green color are key traits farmers seek in amaranth and jute mallow. Tolerance to drought was a preferred trait among farmers for all three crops. Okra producers preferred early maturing varieties bearing a high number of fruits per plant. Regardless of the crop, traders and consumers had similar trait preferences. Leaf physical integrity, green to dark green, and broad leaves were priority traits for amaranth and jute mallow. In okra and jute mallow, high mucilage content was a key attribute. The trait preferences varied between different types of value chain actors, but were consistent for the same types of actors across locations. This research provides foundational information for plant breeders to develop market-preferred varieties, eventually contributing to the greater availability, acceptability, and affordability of TAV.